Sistema web de administración de ventas en base a la gestión por procesos (BPM) para la empresa muebles Sani - Sani Tugumbango, Diego Andrés (2023)
The automation of sales processes through a web application is a technological strategy that allows improving efficiency and productivity for the Muebles Sani company, because the business process model allows the development of a technological solution that made it possible to streamline and optimize all stages of the sales cycle, from customer acquisition to furniture delivery. The Extreme Programming development methodology is an agile approach that focuses on requirements specification, software modeling, development, testing and integration which facilitates the development of the software product according to the needs and requirements of the company. As a result, a modular web application was developed which allows the management of clients (front), orders, proformas and the global management of the system (Back), allowing improvement in the delivery of data and information according to the contracted products. and manufactured by the company.